Clinical Prognostic Factors in Patients With Metastatic Adrenocortical Carcinoma Treated With Second Line Gemcitabine Plus Capecitabine Chemotherapy - Grisanti, Salvatore; Cosentini, Deborah; Laganà, Marta; Morandi, Alessandra; Lazzari, Barbara; Ferrari, Laura; Volta, Alberto Dalla; Ambrosini, Roberta; Ferrari, Vittorio Domenico; Sigala, Sandra; Berruti, Alfredo (Frontiers in Endocrinology, 2021)
Gemcitabine plus Capecitabine (Gem/Cape) is a frequently adopted second line chemotherapy for metastatic adrenocortical carcinoma (ACC), but only a minority of patients is destined to obtain a clinical benefit. The identification of baseline predictive factors of efficacy is relevant. We retrospectively analyzed clinical data from 50 consecutive patients with metastatic progressing ACC treated between 2011 and 2019. Patients received intravenous Gemcitabine and oral Capecitabine on a metronomic schedule. Previous mitotane therapy was maintained. Clinical benefit (partial response + stable disease) at 4 months was 30%, median progression-free survival (PFS) and disease-specific survival (DSS) from Gem/Cape start were 3 and 8 months, respectively. Among clinical variables evaluated before the start of Gem/Cape, presence of ECOG performance status ≥1 (HR 6.93 95% Confidence Interval (CI] 0.03-0.54, p .004) and neutrophil-to-lymphocyte ratio (NLR) ≥5 (HR 3.88, 95% [CI] 0.81-0.90, p .003) were independent indicators of poor PFS at multivariate analysis. Conversely, surgery of primary tumor, the presence of lung or lymph-node metastases, blood mitotane level, anemia and the Advanced Lung cancer Inflammation index (ALI) failed to be independently associated. This study confirms that the Gem/Cape schedule is modestly active in heavily pretreated ACC patients (28% received at least 2 previous chemotherapy lines). NLR and performance status (PS) are easily available clinical parameters that are helpful to identify patients not likely to derive significant advantage from Gem/Cape chemotherapy.